Osteoprotegerin, Soluble Receptor Activator of Nuclear Factor-κB Ligand, and Subclinical Atherosclerosis in Children and Adolescents with Type 1 Diabetes Mellitus. (30th October 2013) - Lambrinoudaki, Irene; Tsouvalas, Emmanouil; Vakaki, Marina; Kaparos, George; Stamatelopoulos, Kimon; Augoulea, Areti; Pliatsika, Paraskevi; Alexandrou, Andreas; Creatsa, Maria; Karavanaki, Kyriaki
Abstract : Aims . To evaluate carotid intima-media thickness (cIMT) and biomarkers of the osteoprotegerin/receptor activator of nuclear factor- κ B ligand (OPG/RANKL) system in type 1 diabetes (T1DM) children and adolescents and controls. Subjects and Methods . Fifty six T1DM patients (mean ± SD age: 12.0 ± 2.7 years, diabetes duration: 5.42 ± 2.87 years and HbA1c: 8.0 ± 1.5%) and 28 healthy matched controls, were studied with anthropometric and laboratory measurements, including serum OPG, soluble RANKL (sRANKL) and cIMT. Results . Anthropometric, laboratory, and cIMT measurements were similar between T1DM youngsters and controls. However patients with longer diabetes duration (>/7.0 years) had indicatively higher cIMT (cIMT = 0.49 vs 0.44 mm, P 0.072) and triglyceride levels than the rest of the patients (93.7 vs 64.6 mg/dl, P 0.025). Both in the total study population (β 0.418, P 0.027) and among T1DM patients separately (β 0.604, P 0.013), BMI was the only factor associated with cIMT. BMI was further associated with OPG in both groups (β −0.335, P 0.003 and β −0.356, P 0.008 respectively), while sRANKL levels were not associated with any factor. Conclusions . BMI was the strongest independent predictor of cIMT among the whole population, and especially in diabetics, suggesting a possible synergistic effect of diabetes and adiposity on atherosclerotic burden. BMI was overall strongly associated with circulating OPG, but the causes of this association remain unclear.